1994
DOI: 10.1007/bf00144124
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed mutagenesis of the ferric uptake regulation gene of Escherichia coli

Abstract: The 12 histidine and four cysteine residues of the Fur repressor of Escherichia coli were changed, respectively, to leucine and serine by site-directed mutagenesis of the fur gene. The affects of these mutations were measured in vivo by ligation of the mutated genes to a wild-type fur promoter followed by measurement of the ability of these plasmids to regulate expression of a lacZ fusion in the aerobactin operon. In vitro affects were assayed by insertion of the mutated genes in the expression vector pMON2064… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
64
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 28 publications
9
64
1
Order By: Relevance
“…This change in the metal environment could alter the conformation of the protein and, therefore, modify the ability of Fur to bind to DNA. On this purpose, site-directed mutagenesis experiments have shown that a single mutation of residue likely involved in Fe 2ϩ coordination yields an inactive Fur protein (45,46). Mutation especially of His-90, a highly conserved amino acid in Fur sequences, leads to an inactive protein still able to dimerize (45).…”
Section: Discussionmentioning
confidence: 99%
“…This change in the metal environment could alter the conformation of the protein and, therefore, modify the ability of Fur to bind to DNA. On this purpose, site-directed mutagenesis experiments have shown that a single mutation of residue likely involved in Fe 2ϩ coordination yields an inactive Fur protein (45,46). Mutation especially of His-90, a highly conserved amino acid in Fur sequences, leads to an inactive protein still able to dimerize (45).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is interesting that the Bacillus subtilis Fur apparently does not require Fe# + for DNA binding activity in vitro (Bsat & Helmann, 1999). Ligands to the structural Zn# + ion are believed to include Cys-92 and Cys-95, which have been shown to be essential for normal Fur activity in E. coli (Coy et al, 1994 ;Gonzalez de Peredo et al, 1999). Indeed, amongst a collection of Fur proteins substituted at all cysteine and histidine residues, those in which Cys-92 or Cys-95 were replaced by serine had much the most severe phenotypes (Coy et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The x-ray absorption spectroscopy of Escherichia coli Fur (Fur EC ) revealed Zn 2ϩ bound in a tetrahedral environment composed of two S and two N/O donor ligands (4). Subsequent studies using chemical modification and mass spectroscopy assigned Cys 92 and Cys 95 as Zn 2ϩ ligands (5), a conclusion supported by site-directed mutagenesis studies (6). To date, the only structure available for a protein from the Fur superfamily is Pseudomonas aeruginosa Fur (Fur PA ) that was crystallized in the presence of Zn 2ϩ (7).…”
mentioning
confidence: 97%